2014
DOI: 10.4236/jssm.2014.75034
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of the Effect of Social Media Marketing on Online Shopping of Customers by Mediating Variables

Abstract: The present study aimed to evaluate the effect of social media marketing on online shopping of customers based on mediating role of value capital, relational capital and brand capital by path analysis method. 169 students of Tehran University were included in this study. They filled out the questionnaires of social media marketing, value capital, relational capital, brand capital and eshopping of customers. The results of path analysis showed that social media marketing had positive and significant impact on v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 19 publications
0
5
0
1
Order By: Relevance
“…While maximum organizations were still grappling with social media accountability, the usage of the CIE and CIV metrics gave Hokey Pokey a significant competitive edge [12]. Alireza M et al conducted a study on social media marketing on online shopping of customers and concluded that social media resulted in friendly relations resulted in friendly relations, one hypothesis showed that awareness of services and products of company increases brand capacity both the studies does not give the idea about the effect of social media -Facebook on increased sales of different products [13] Research Question: What is the impact of Social Media -Facebook in new age marketing?…”
Section: Literature Reviewmentioning
confidence: 99%
“…While maximum organizations were still grappling with social media accountability, the usage of the CIE and CIV metrics gave Hokey Pokey a significant competitive edge [12]. Alireza M et al conducted a study on social media marketing on online shopping of customers and concluded that social media resulted in friendly relations resulted in friendly relations, one hypothesis showed that awareness of services and products of company increases brand capacity both the studies does not give the idea about the effect of social media -Facebook on increased sales of different products [13] Research Question: What is the impact of Social Media -Facebook in new age marketing?…”
Section: Literature Reviewmentioning
confidence: 99%
“…V. Kumar and Rohan Mirchandani conducted a study on the increasing return of interest of social media marketing at consumer as well as company level, a specific campaign impact when done on Facebook and Twitter but does not provide insights on effect of digital marketing done by means of Instagram [13]. Alireza M et al conducted a study on social media marketing on online shopping of customers and concluded that social media resulted in friendly relations resulted in friendly relations, one hypothesis showed that awareness of services and products of company increases brand capacity both the studies does not give the idea about the effect of social media -Instagram on increased sales of different products [14]. 1 shows the questionnaire form distributed in the park and the college and the survey form filled by candidates who were the regular users of social media platform especially Instagram were selected for the survey.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Additionally, organizations' interest in social media is derived by numerous benefits organizations can achieve such as reducing cost, increasing profitability, sharing knowledge and building business partnerships (Neti, 2011). Hence, researchers have studied social media and social media marketing in different domains such as the impact of social media on customers (Hajli, 2013); effects of social media marketing on online consumer behavior (Vinerean, Cetina, & Tichindelean, 2013); the effect of social media marketing on online shopping (Mohammadpour, Roshandel Arbatani, Hassan Holipour, Farzianpour, & Hosseini, 2014), social media strategies (Bajpai, Pandey and Shriwas, 2012); creative strategies in social media marketing (Ashley & Tuten, 2015); impact of social media marketing on brand loyalty and purchase intention (Balakrishnan, Dahnil, & Yi, 2014); antecedents of social media marketing application (Brech, Messer, Schee, Rauschnabel, & Ivens , 2017); foundations of social media marketing (Constantinides, 2014); effectiveness of social media such as Facebook advertising in enhancing purchase intention (Dehghani & Tumer, 2015); impact of social media marketing on brand loyalty (Erdogmus & Cicek, 2012); antecedents of social media analysis (Guede, Curiel, & Antonovica, 2017); the impact of user interactions in social media on brand awareness and purchase intention (Hutter, Hautz, Dennhardt, & Füller, 2013); corporate reputation and customer behavioral intentions (Keh & Xie, 2008) social media marketing and brand equity (Zahoor & Qureshi, 2017).…”
Section: Social Media Marketingmentioning
confidence: 99%